Drosophila as a model organism homeotic genes and development in an animal - Orr-Weaver, Terry L.; Lodish, Harvey F. (New York : Cogito Learning Media, 1996)
Described about Drosophila melanogaster that has been subjected to extensive genetic analysis for almost 90 years
Video is accompanied by a user's manual
Copy available in DVD format
Series editor, Harvey F. Lodish
Keywords: Drosophila; Drosophila -- Genetics; Organisms